Ответы и объяснения

2013-06-04T09:57:46+00:00

\int x \ln(x^2+1)dx = \frac{1}{2}\int(\ln(x^2+1))d(x^2+1) = \frac{1}{2}\int(\ln t)dt

Интегрирование логарифма производится по частям

представим, что

u = \ln t; v = t\\ du = u'dt = \frac{dt}{t}\\ dv = v'dt = dt\\ \int \ln t dt = \int u dv = uv - \int vdu = t \ln t - \int t\frac{dt}{t} = \\ = t \ln t - \int dt = t \ln t - t +C

далее вернемся к нашему интегралу:

\frac{1}{2}\int \ln t dt =\frac{t \ln t - t}{2} + C = \frac{x^2+1}{2}\ln (x^2+1) - \frac{x^2+1}{2} + C = \\ =\frac{x^2+1}{2}\ln(\frac{x^2+1}{e}) + C